Calf feeding and management: Effect of genotype (Bos taurus x Bos indicus), level of milk feeding and type of housing on the pre-weaning performance of crossbred calves - Osuji, P.O.; Yimegnuhal, A.; Umunna, N.N.; Tegegne, Azage (Ethiopian Society of Animal Production, 2000)
The effect of genotype (50%, 75% and 87.50, levels of milk (2 and 3 1/day) and types of housing (Barn and Hutch) on growth and survival were examined using thirty four crossbred calves Boran x Freisian (Bos Taurus x Bos indicus). Calves had access to a complete diet supplement (180 g/kg CP and 100 g/kg roughage) and were weaned when supplement intake reached 450 g/day for two consecutive days. Supplement dry matter intake of calves housed in the Barn was significantly higher (p<0.05) than for calves housed in the hutch. An. increase in supplement and milk intake was observed in 50% crossbred calves. There was significant interaction effect between the levels of milk and types of housing on supplement intake (p<0.05). Average daily gain (ADG) of 50%, 75% and 87.5% crossbred calves was 316, 299 and 286 g/day (SE .± 23.99) while weaning age was 52.9, 45.9 and 39.8 days (SE± 4.33) respectively. Weaning weight of 50%, 75% and 87.5% crossbred calves fed on 3 1/day was 48.9, 44.5 and 40.1 kg (SE± 1.32) and those offered 2 1/day was 41.2, 38.6 and 38.7 kg (SE ±1.24), respectively and were not significantly different (p>0.05). However, mean weaning weight of crossbred calves with 50% exotic blood level was superior than the 75% and 87.5% (p<0.05) for both levels of milk feeding. The result indicates that early weaning of crossbred calves with 50% exotic blood through subsequent introduction of complete diet supplementation from day four after birth will reduce the quantity of milk consumed per calf per day. The reduction of consumable milk by calves would avail smallholder farmers with surplus milk for his household consumption and / or for sale to generate extra income.